Radio beacon and radar assessment and forecasting of equatorial F region ionospheric stability - Hysell, D. L. (2019)
Ionospheric conditions on two adjacent nights in March 2019 were observed at the Jicamarca Radio Observatory using a combination of incoherent scatter, coherent scatter, and high‐frequency (HF) radio modes. The HF data came from a network of beacons consisting of three transmitters and six receivers operating at two frequencies and deployed regionally. The HF beacons employ pseudorandom noise coding and can be used to measure group delay (pseudorange) and Doppler shift, and the time derivative of optical path length. A method for inferring volumetric estimates of electron density regionally from the HF data is described. The radar and HF data are interpreted in light of a direct numerical simulation of the ionospheric interchange instability to elucidate why convective plumes and equatorial spread F conditions occurred on one night but not the other. The numerical simulation accurately predicted whether convective plumes would develop on a given night, utilizing initial conditions and forcings derived from the incoherent scatter data. The HF data were consistent with the incoherent scatter observations and remained intelligible throughout the equatorial spread F event. Crests in the bottomside electron density associated with convective plumes at higher altitudes could be seen propagating through the region in the HF data. It should be possible to incorporate HF data in assimilative simulations of interchange instabilities in order to predict where and when individual convective plumes emerge.